Effect of Clinical Research Development Center on the Process of Evidence Based Clinical Researches in Shahid Beheshti Hospital - Hamid Shafi; Neda Amani; Atekeh Babazadeh; Mohaddeseh Mirzapour; Ali Bijani (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE: Information revolution with a wide range of effectiveness, in different dimensions of the society, especially in medical sciences can be a way for solving the problems. METHODS: This study was before- after intervention HSR type research and clinical faculty members of Shahid Beheshti Hospital in Babol, comprised the statistical population. With establishment of clinical research development unit in Shahid Beheshti Hospital in 2009, the provided services in this center, the number of published papers and the number of approved research projects and theses were considered as indicators of research performance. These indicators were calculated before and after the center establishment. For data collection, information in the database of faculty research system were used. The number of theses and published articles were asked from the faculty members. FINDINGS: Research activities of faculty in research projects, theses and published papers, before the establishment of the unit, were 58 cases (25.9%), and after that, 166 cases (74.10%). The contribution of this clinical research development unit in the improvement of research goals of Babol University of Medical Sciences, based on the number of published papers according to the type of the article and the indices of journals which articles have been published in, has been 84.5 since the time of the center establishment . CONCLUSION: Significant growth in the number, research projects per capita, approved articles and theses indicates a positive effect on the research consultations in database and increase in research attitude and interest of practitioners and students.